A land of books : dreams of young Mexihcah word painters - Tonatiuh, Duncan (Abrams Books for Young Readers, 2022)
Illustrations and text describe how the Mixtecs create painted manuscripts, or codices, that reflect their way of life and document their history, science, land tenure, tribute, and sacred rituals.